-6+-x+12x=10x+6

Simple and best practice solution for -6+-x+12x=10x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+-x+12x=10x+6 equation:


Simplifying
-6 + -1x + 12x = 10x + 6

Combine like terms: -1x + 12x = 11x
-6 + 11x = 10x + 6

Reorder the terms:
-6 + 11x = 6 + 10x

Solving
-6 + 11x = 6 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-6 + 11x + -10x = 6 + 10x + -10x

Combine like terms: 11x + -10x = 1x
-6 + 1x = 6 + 10x + -10x

Combine like terms: 10x + -10x = 0
-6 + 1x = 6 + 0
-6 + 1x = 6

Add '6' to each side of the equation.
-6 + 6 + 1x = 6 + 6

Combine like terms: -6 + 6 = 0
0 + 1x = 6 + 6
1x = 6 + 6

Combine like terms: 6 + 6 = 12
1x = 12

Divide each side by '1'.
x = 12

Simplifying
x = 12

See similar equations:

| 1/2y=y-6 | | x+16=5x-40 | | 12+-2y=12+5y | | 27=2x+11 | | 6x+20-3(2x+6)=5x+12 | | 2.5+2.25x=9.25 | | x+x=98 | | 2.1=-w+2.5 | | 12+-2y=15+-4.5y | | 26+2x=0 | | 2=1y-5x | | 12x-24=3(4x+8) | | 0.25c+30=59.5 | | 12+-2y=15+-4y | | 0=16x^2-25x^4 | | 2x+20+48x=180 | | (x+26)2=246 | | x+2+5=5 | | 14=-2s+18 | | 2x+8y=30 | | 40-3c-4=4c+20+c | | 20z=10 | | 0=-16t^2+vt+27000 | | (2x)+(3x+14)=109 | | 20.3=-9h+29.3 | | 3x^2=-64 | | 8*5+8*1-2*6+6-2*2-1= | | 5n+36=-7.2 | | 20.3=-9h+293 | | (x+12)squared=100 | | y=-1.5x-1.4 | | 5m+36= |

Equations solver categories